Asuhan keperawatan untuk masalah keperawatan nyeri akut pada ibu post sectio cesarea (sc) dengan penerapan imajinasi terbimbing (guided imagery) - Budiarti Budiarti; Aryanti Wardyah; Rilyani Rilyani (THE JOURNAL OF Mother and Child Health Concerns, 2023)
Background: At Abdul Moeloek Regional General Hospital, the incidence of maternal delivery using the Sectio Caesarea (SC) method in 2019 was 528 people, in 2020 it was 663 people, and in 2021 it was 678 people. In 2022, the incidence of maternal delivery using the Sectio Caesarea (SC) method was 643 people, while in 2023 there were 684 people and this shows that there has been a decrease and increase in the incidence of maternal delivery using the Sectio Caesarea (SC). CS delivery causes several complications, one of which is pain in the incision area or tearing of tissue in the abdominal wall and uterus. The level of pain will be felt more than 12 hours after surgery. The therapy used is non-pharmacological therapy to reduce pain from cesarean section, if with non-pharmacological therapy, namely guided imagery techniques. Purpose: To determine the effect of applying guided imagery in reducing pain in post-section cesarean (SC) patients at Abdul Moeloek Regional General Hospital, Bandar Lampung. Method: This research is a descriptive research with a case study approach. The subjects in this study were two respondents who suffered from post-cesarean section (SC) in the obstetrics room of Abdul Moeloek Hospital. Result: Nursing care has been carried out on post-cesarean section (SC) mothers with the application of guided imagery therapy in the obstetrics room of Abdul Moeloek Hospital. The management of acute pain nursing with the application of Guided imagery nursing actions that the author carried out for 3 days found active pain problems in post-cesarean section (SC) mothers where the problems of both clients were all resolved as evidenced by the clients Mrs. A and Mrs. M normal pain scale and during the action both clients were cooperative. Conclusion: There is an effect of the application of Guided imagery to reduce pain in post-cesarean section (SC) mothers. Keywords: Guided Imagery; Pain; Sectio Caesarea. Pendahuluan: Di Rumah Sakit Umum Daerah Abdul Moeloek angka kejadian persalinan ibu dengan metode Sectio Caesarea (SC) pada tahun 2019 sebanyak 528 orang, tahun 2020 sebanyak 663 orang, dan pada tahun 2021 sebanyak 678 orang. Pada tahun 2022 angka kejadian persalinan Ibu dengan metode Sectio Caesarea (SC) pada 643 orang sedangkan ditahun 2023 terdapat 684 orang dan hal tersebut menunjukkan bahwa terjadi penurunan dan peningkatan angka kejadian persalinan ibu secara Sectio Caesarea (SC). Persalinan SC memunculkan beberapa komplikasi salah satunya adalah nyeri pada daerah insisi atau robekannya jaringan pada dinding perut dan uterus. Tingkat nyeri akan terasa lebih dari 12 jam pasca operasi. Terapi yang digunakan ialah terapi non farmakologi untuk mengurangi nyeri sectio caesarea, apabila dengan terapi non farmakologi yaitu teknik imajinasi terbimbing atau Guided imagery. Tujuan: Untuk mengetahui pengaruh penerapan guided imagery dalam mengurangi rasa nyeri pada pasien post sectio cesarea (SC) di Rumah Sakit Umum Daerah Abdul Moeloek Bandar Lampung. Metode: Penelitian ini adalah jenis penelitian deskristif dengan pendekatan studi kasus.  Subjek dalam deng penelitian ini adalah penderita ibu post sectio cesarea (SC) sebanyak dua responden yang ada di ruang kebidanan RSUD Abdul Moeloek. Hasil: Telah dilaksanakan asuhan keperawatan pada ibu post sectio cesarea (SC) dengan penerapan terapi imajinasi terbimbing (guided imagery) di ruang kebidanan RSUD Abdul Moeloek. Pengelolaan  keperawatan nyeri akut dengan  penerapan  tindakan  keperawatan Guided imagery yang  penulis  lakukan  selama  3  hari  didapatkan  masalah  nyeri aktif  pada ibu post sectio cesarea (SC) dimana masalah kedua  klien  teratasi  semua  dibuktikan  dengan klien  ny. A dan Ny. M skala nyeri normal dan selama tindakan kedua klien koperatif. Simpulan: Terdapat pengaruh penerapan Guided imagery untuk mengurangi nyeri pada pasien ibu post sectio cesarea (SC).